(untitled) (Comparatismi, 2022)
The essay analyses the modalities of a narrative of trauma understood as a daily and prolonged exposure to a context of a systemic violence, such as that expressed in our society by its deeply-rooted patriarchal structures. To this end, the essay focuses on two recent Italian texts, a novel and an autobiographical testimony, which stand out within a generalized discourse aimed at presenting rape and femicide as punctual events, emergencies isolated from the roots of a wider context of violence, perpetuated by the forms and institutions of dominant culture.